2023
DOI: 10.3389/fenrg.2022.1047254
|View full text |Cite
|
Sign up to set email alerts
|

Performance optimization and kinetic analysis of HNO3 coupled with microwave rapidly modified coconut shell activated carbon for VOCs adsorption

Abstract: As a typical carbon-based material, activated carbon (AC) has satisfied adsorption performance and is of great significance in the field of volatile organic compounds (VOCs) pollutants removal. In order to further reveal the optimization mechanism of AC adsorption performance, coconut shell-based AC was selected as the research object, and different concentrations of HNO3 coupled with microwave were used for rapid modification and activation. The characteristic changes of pore structure and surface chemical of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Several studies have shown that modifying activated carbon can significantly improve its physical and chemical characteristics, which in turn enhance adsorption selectivity and capacity . Activated carbon modification is generally implemented using acid treatment, base treatment, microwave irradiation, ozone oxidation, impregnation with hydrophilic chemicals, and grafting of hydrophilic functional groups connected to the activated carbon surface. , Acid treatment or base treatment is usually performed by immersing the activated carbon in different solutions, which is followed by filtration and drying. However, the drying process of wet-modified activated carbon is extremely prone to cause fires if the temperature increase due to heat accumulation exceeds its ignition temperature. , The increasing number of applications in the activated carbon modification industry and the frequent occurrence of combustion in the process of modifying activated carbon have necessitated additional studies on the safety research and combustion prevention …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that modifying activated carbon can significantly improve its physical and chemical characteristics, which in turn enhance adsorption selectivity and capacity . Activated carbon modification is generally implemented using acid treatment, base treatment, microwave irradiation, ozone oxidation, impregnation with hydrophilic chemicals, and grafting of hydrophilic functional groups connected to the activated carbon surface. , Acid treatment or base treatment is usually performed by immersing the activated carbon in different solutions, which is followed by filtration and drying. However, the drying process of wet-modified activated carbon is extremely prone to cause fires if the temperature increase due to heat accumulation exceeds its ignition temperature. , The increasing number of applications in the activated carbon modification industry and the frequent occurrence of combustion in the process of modifying activated carbon have necessitated additional studies on the safety research and combustion prevention …”
Section: Introductionmentioning
confidence: 99%
“… 9 Several studies have shown that modifying activated carbon can significantly improve its physical and chemical characteristics, which in turn enhance adsorption selectivity and capacity. 10 Activated carbon modification is generally implemented using acid treatment, 11 base treatment, 12 microwave irradiation, 13 ozone oxidation, 14 impregnation with hydrophilic chemicals, and grafting of hydrophilic functional groups connected to the activated carbon surface. 15 , 16 Acid treatment or base treatment is usually performed by immersing the activated carbon in different solutions, which is followed by filtration and drying.…”
Section: Introductionmentioning
confidence: 99%
“…Different countries or organizations have different definitions for VOCs [1]. According to the World Health Organization (WHO), VOCs refer to a variety of organic compounds with boiling points ranging from 50 to 260°C under normal atmospheric pressure [2]. In China, VOCs are defined as organic compounds with a saturated vapor pressure greater than 70.91 Pa at room temperature, standard atmospheric pressure of 101.3 kPa, boiling points below 50-260°C, and an initial boiling point equal to 250°C [3].…”
Section: Introductionmentioning
confidence: 99%